It's time to sleep, my love - Metaxas, Eric (Feiwel & Friends, 2008)
As children prepare for bed, the world around them is also settling down for the night. Through the seasons, animals who live in the jungle, the forest, and the sea all whisper to their babies, and to yours, a soft refrain: "It's time to sleep, my love."